Driving Factors Behind Turkey's Establishment of The Turkey-Russia Joint Center in 2020 - Ismiyatun, Ismiyatun; Purwono, Andi; Maulida, Novianda (Riwayat: Educational Journal of History and Humanities, 2025)
The Nagorno-Karabakh conflict is a territorial dispute between Armenia and Azerbaijan in 2020 that attracted the attention of international actors, especially Turkey and Russia. In times of peace of conflict, Turkey entered into an agreement with Russia to carry out the construction of the Turkish-Russian Joint Center. The purpose of this study is to find out the factors that are the reasons for Turkey to make an agreement with Russia in establishing a Joint Turkish-Russian Center. Using qualitative descriptive research methods with data and information collection techniques in accordance with references from books, journals, and articles on the web. The theory used is the decision-making theory initiated by Richard Snyder, H.W. Bruck, and Burton Sapin, that "the actions of a country are foreign policies that are influenced by internal and external conditions". The first is Turkey's dependence on Russia in nuclear projects and agreements on the purchase of military equipment, while in the external sphere there is a great influence of Russia's geopolitics in the Caucasus region as well as in the conflict.